Α-Pinene-Derived organic coatings on acidic sulfate aerosol impacts secondary organic aerosol formation from isoprene in a box model. (15th September 2019) - Schmedding, Ryan; Ma, Mutian; Zhang, Yue; Farrell, Sara; Pye, Havala O.T.; Chen, Yuzhi; Wang, Chi-tsan; Rasool, Quazi Z.; Budisulistiorini, Sri H.; Ault, Andrew P.; Surratt, Jason D.; Vizuete, William
Abstract: Fine particulate matter (PM2.5 ) is known to have an adverse impact on public health and is an important climate forcer. Secondary organic aerosol (SOA) contributes up to 80% of PM2.5 worldwide and multiphase reactions are an important pathway to form SOA. Aerosol-phase state is thought to influence the reactive uptake of gas-phase precursors to aerosol particles by altering diffusion rates within particles. Current air quality models do not include the impact of diffusion-limiting organic coatings on SOA formation. This work examines how α -pinene-derived organic coatings change the predicted formation of SOA from the acid-catalyzed multiphase reactions of isoprene epoxydiols (IEPOX). A box model, with inputs provided from field measurements taken at the Look Rock (LRK) site in Great Smokey Mountains National Park during the 2013 Southern Oxidant and Aerosol Study (SOAS), was modified to incorporate the latest laboratory-based kinetic data accounting for organic coating influences. Including an organic coating influence reduced the modeled reactive uptake when relative humidity was in the 55–80% range, with predicted IEPOX-derived SOA being reduced by up to 33%. Only sensitivity cases with a large increase in Henry's Law values of an order of magnitude or more or in particle reaction rates resulted in the large statistically significant differences form base model performance. These results suggest an organic coating layer could have an impact on IEPOX-derived SOA formation and warrant consideration in regional and global scale models. Highlights: Relative Humidity dependent Dorg showed limited effects on IEPOX reactive uptake. Increasing inorganic and organic Henry's Law coefficients improved model performance. Concentrating inorganic species into the aerosol core improved model performance.